Study on Equilibrium of Sulfur Species in Model Oil with Ionic Liquid - Abdul Hadi Azimi bin Abd. Wahab, Abdul Hadi Azimi (UNIVERSITI TEKNOLOGI PETRONAS, 2011)
Extraction of thianaphthene, one of the long sulfur chain existed in crude oil from model oil (which is dodecane in this study) is experimentally carried out by using an ionic liquid 1-butyl-3-methylimidazolium octyl sulfate. Result from the experiment is expressed as a ternary diagram. The objective of this study is to investigate the efficiency of the experimented ionic liquid as an extractor of long sulfur chain from model oil which can be used later to as a base comparison with another extractor. This report will be divided into 4 parts which consist of introduction, which includes abstract, problem statement, and objective scope of study. Next part of this report will be covered on literature review which includes a brief introduction on equilibrium, and material used in the study. Methodology will be in the third chapter as all the methodology used to conduct the experiment is reported in this section. At the end of the report, details on result and discussion will be explained on last part of the report which is part 4.